Sulphur boosts cashews - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Tanzanian cashew output increased sharply from 63,000 tons in 1996-1997 to 121,207 tons in 1999-2000 according to the Tanzanian Ministry of Agriculture and Food Security. Cashew nut is the country s fourth most valuable export crop. The government...